Pete the cat and his magic sunglasses - Dean, James, 1957- (Pete the cat., 2013)
"Pete the Cat wakes up feeling grumpy--nothing seems to be going his way. But with the help of some magic sunglasses, Pete learns that a good mood has been inside him all along"--